Family functioning of elderly with depressive symptoms - Rosely Almeida Souza; Gislaine Desani da Costa; Cintia Hitomi Yamashita; Fernanda Amendola; Jaqueline Correa Gaspar; Márcia Regina Martins Alvarenga; Odival Faccenda; Maria Amélia de Campos Oliveira (SciELO, 2014)
Objective: To classify families of elderly with depressive symptoms regarding their functioning and to ascertain the presence of an association between these symptoms, family functioning and the characteristics of the elderly. Method: This was an observational, analytical, cross-sectional study performed with 33 teams of the Family Health Strategy in Dourados, MS. The sample consisted of 374 elderly divided into two groups (with and without depressive symptoms). The instruments for data collection were a sociodemographic instrument, the GeriatricDepression Scale (15 items) and the Family Apgar. Results: An association was observed between depressive symptoms and family dysfunction, female gender, four or more people living together, and physical inactivity. Conclusion: The functional family may represent effective support for the elderly with depressive symptoms, because it offers a comfortable environment that ensures the well-being of its members. The dysfunctional family can barely provide necessary care for the elderly, which can exacerbate depressive symptoms.